Formulation of Chicken Nuggets with the Addition of Chicken Liver as a Product Rich in Iron and Vitamin A for Adolescent Females - Wibisono, Himawan Haryo; Aries, Muhammad; Nasution, Zuraidah (Jurnal Gizi dan Pangan, 2023)
The purpose of this study was to develop chicken nuggets with the addition of chicken liver and analyze their nutritional content. Nugget with 10% chicken substituted with chicken liver was the selected formulation. The nutrient profile of the selected nugget formula was: 56.8 g/100 g moisture, 1.46 g/100 g ash, 14.66 g/100 g protein, 6.5 g/100 g fat, 12.92 g/100 g carbohydrates, 16.39 mg/100 g iron, and 760.16 RE /100 g vitamin A. One serving of the selected nugget formula is equivalent to 100 g (4 pieces) that contribute 168 kcal energy. The selected formulations have met the claims for low fat, high in iron and vitamin A, and source of protein.